Peningkatan Kapasitas Kewirausahaan Melalui Teknologi Tepat Guna Dan Strategi Pemasaran Digital Pada UMKM Industri Sirup Di Kudus - Zahro, Nafi’ Inayati; Fiati, Rina; Kusumodestoni, Raden Hadapiningradja; Sumekar, Kertati (Journal of Dedicators Community, 2025)
Kudus is one of the districts on the north coast of Central Java which has a prominent entrepreneurial tradition. There are also many types of factories and MSME businesses. All of this gives Kudus Regency its own style as a city of industry and trade. One of the MSME industries that also promotes the local wisdom culture of the city of Kudus is the herbal ginger and parijoto syrup industry typical of the Muria mountains, namely the UMKM UD Yogas Delima and CV Seleksi Alam Muria. The aim of this service activity is to encourage the development of SMEs in increasing competitiveness and improving product quality with digital marketing-based information technology, handling aspects of production, human resources, management, administration and production, as well as improving the skills of entrepreneurs, improving quality and quantity, and management. good management. The implementation method prioritizes product improvements by exploring raw materials, product design, marketing, improving HR soft skills and marketing. Implementation of activities includes mentoring, training and creation of appropriate technological tools as well as procedures and use of appropriate technological tools which are transferred to partners